1999
DOI: 10.1053/euhj.1998.1353
|View full text |Cite
|
Sign up to set email alerts
|

A randomized evaluation of early revascularization to treat shock complicating acute myocardial infarction. The (Swiss) Multicenter Trial of Angioplasty for Shock—(S)MASH

Abstract: We failed to demonstrate that emergency PTCA significantly improves survival in patients with acute myocardial infarction and early cardiogenic shock. Because the study was stopped prematurely, due to an insufficient patient inclusion rate, a clinically meaningful benefit of early reperfusion may have been missed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
0
4

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(94 citation statements)
references
References 17 publications
4
86
0
4
Order By: Relevance
“…19 The higher mortality rates in that trial (69 percent among patients assigned to emergency revascularization and 78 percent among patients assigned to medical therapy) than in our trial were consistent with the requirement that patients have no response to initial supportive measures. The 9 percent absolute difference between the groups in 30-day mortality was the same as that in our study.…”
Section: Comparison With Prior Studiessupporting
confidence: 84%
See 1 more Smart Citation
“…19 The higher mortality rates in that trial (69 percent among patients assigned to emergency revascularization and 78 percent among patients assigned to medical therapy) than in our trial were consistent with the requirement that patients have no response to initial supportive measures. The 9 percent absolute difference between the groups in 30-day mortality was the same as that in our study.…”
Section: Comparison With Prior Studiessupporting
confidence: 84%
“…16,17 A prematurely terminated randomized trial comparing angioplasty with conventional therapy for shock in 55 patients reported no difference in mortality. 19 Most patients with cardiogenic shock do not undergo emergency revascularization, either because of the lack of facilities at the hospitals where they present or because of doubt as to its efficacy. 18,[20][21][22] If early revascularization reduces mortality, angioplasty or coronary-artery bypass graft surgery should be performed on an urgent basis, even if this requires transfer to a hospital with the necessary facilities and expertise.…”
Section: Discussionmentioning
confidence: 99%
“…The benefit was similar in the incomplete, randomized Swiss Multicenter Study of Angioplasty for Shock. 56 Numerous registry studies have confirmed the survival advantage of early revascularization, whether percutaneous or surgical, in the young and the elderly. Thrombolytic therapy is less effective but is indicated when PCI is impossible or if a delay has occurred in transport for PCI and when MI and CS onset were within 3 hours.…”
Section: Reperfusionmentioning
confidence: 99%
“…The higher mortality rate may have been due to the inclusion of sicker patients that remained hypotensive despite inotropic support and volume replacement. This study terminated early because of difficulties in patient recruitment 42 .…”
Section: I) Revascularization In Multivessel Coronary Artery Diseasementioning
confidence: 99%